Happiness Uncovered: Exploring Subjective Well-being among Female Students in Islamic Boarding School - Febriana, Siti Nabila; Noveyani, Adistha Eka; Safitri, Fita Auwalina Ayu (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Subjective well-being is a measurement that can be used to integrate mental health as disease prevention and health promotion. Objective: This study aims to determine the relationship between subjective well-being and mental health in female students at an Islamic boarding school. Methods: This study is an observational analytic with a cross-sectional approach. The population is 179 female students; 100 samples were obtained using simple random sampling. The variables in this study are subjective well-being and mental health, optimism, gratitude, and self-esteem. Bivariate data analysis used the Spearman correlation test. Discussion: The result found that female students have moderate subjective well-being (66%), moderate mental health (52%), high optimism (84%), high gratitude (60%), and high self-esteem (77%). Correlation analysis shows that there is a relationship between optimism and subjective well-being (0.00<0.05), there is a relationship between gratitude and subjective well-being (0.019<0.05), there is no relationship between self-esteem and subjective well-being (0.619>0.05), and there is a relationship between subjective well-being and mental health (0.04<0.05). Conclusion: Al-Husna Islamic boarding school can maintain subjective well-being in several ways, including by providing learning and education to see life positively, healthy ways of giving thanks, training in positive thinking, and self-development linked to Islamic teachings.